Share

Books Shortlist

# Solution for If X = Sin T, Y = Sin Pt, Prove that ( 1 − X 2 ) D 2 Y D X 2 − X D Y D X + P 2 Y = 0 ? - CBSE (Science) Class 12 - Mathematics

ConceptSimple Problems on Applications of Derivatives

#### Question

If x = sin ty = sin pt, prove that $\left( 1 - x^2 \right)\frac{d^2 y}{d x^2} - x\frac{dy}{dx} + p^2 y = 0$ ?

#### Solution

Here,

$x = \sin t \text { and y } = \sin pt$

$\text { Differentiating w . r . t . t, we get }$

$\frac{d x}{d t} = \cos t \text { and } \frac{d y}{d t} = p \cos pt$

$\Rightarrow \frac{d y}{d x} = \frac{p\cos pt}{\cos t}$

$\text { Differentiating w . r . t . x, we get }$

$\frac{d^2 y}{d x^2} = \frac{- p^2 \sin pt \cos t + p\cos pt\sin t}{\cos^2 t} \times \frac{dt}{dx}$

$\Rightarrow \frac{d^2 y}{d x^2} = \frac{- p^2 \sin pt \cos t + p\cos pt\sin t}{\cos^3 t}$

$\Rightarrow \frac{d^2 y}{d x^2} = \frac{- p^2 \sin pt \cos t}{\cos^3 t} + \frac{p\cos pt\sin t}{\cos^3 t}$

$\Rightarrow \frac{d^2 y}{d x^2} = \frac{- p^2 y}{\cos^2 t} + \frac{x\frac{d y}{d x}}{\cos^2 t}$

$\Rightarrow \cos^2 t\frac{d^2 y}{d x^2} = - p^2 y + x\frac{d y}{d x}$

$\Rightarrow \left( 1 - \sin^2 t \right)\frac{d^2 y}{d x^2} = - p^2 y + x\frac{d y}{d x}$

$\Rightarrow \left( 1 - x^2 \right)\frac{d^2 y}{d x^2} - x\frac{d y}{d x} + p^2 y = 0$

Hence proved.

Is there an error in this question or solution?

#### Video TutorialsVIEW ALL [1]

Solution If X = Sin T, Y = Sin Pt, Prove that ( 1 − X 2 ) D 2 Y D X 2 − X D Y D X + P 2 Y = 0 ? Concept: Simple Problems on Applications of Derivatives.
S